(untitled) (New York, 2017)
The Routledge Handbook of Instructed Second Language Acquisition is the first collection of state-of-the-art papers pertaining to Instructed Second Language Acquisition (ISLA). Written by 45 world-renowned experts, the entries are full-length articles detailing pertinent issues with up-to-date references. Each chapter serves three purposes: provide a review of current literature and discussions of cutting edge issues; share the authors’ understanding of, and approaches to, the issues; and provide direct links between research and practice.
Keywords: Language and languages,Ngôn ngữ.; Study and teaching,Dạy và học